Diagnosis and management of vulvodynia in postmenopausal women. (February 2018) - Vieira-Baptista, Pedro; Donders, Gilbert; Margesson, Lynnette; Edwards, Libby; Haefner, Hope K.; Pérez-López, Faustino R.
Highlights: Vulvodynia is vulvar pain or sensation of burning for more than 3 months, without an identifiable cause. In postmenopausal women, vulvar pain and dyspareunia can often be attributed to low levels of estrogen resulting in vulvovaginal atrophy. Treatment includes general care measures, topical, oral, or injectable agents, psychological approaches, and pelvic floor rehabilitation. In some cases, after failure of other measures, surgery can be considered. No particular intervention has been shown to be superior, so a "trial and error" strategy is usually used. Abstract: Vulvodynia, defined as vulvar pain or burning sensation for more than 3 months, without an identifiable cause, can occur at any age. In this paper, the authors address the classification, epidemiology, etiology, diagnosis, and treatment of this condition, focusing on postmenopausal women. In postmenopausal women, vulvar pain and dyspareunia can often be attributed to low levels of estrogen resulting in vulvovaginal atrophy. While correction of vulvovaginal atrophy is an important part of the management of these patients, it will usually be insufficient to manage vulvodynia. The treatment of vulvodynia includes general care measures, topical, oral, or injectable agents, psychological approaches, pelvic floor rehabilitation and, in some cases, surgery. No particular intervention has been shown to be superior, so a "trial and error" strategy is usually used.